Efficacy of a peer‐based in‐home education program in improving social‐emotional outcomes of parents and children. Issue 5 (1st August 2022) - Koop, Jennifer; Holliday, Daniel; Mathews, Brittany L.; Namaste, Jessica; Alt, Rebecca; Biel, Christa Haring
Abstract: Significant disparities in education and social‐emotional outcomes exist between racial/ethnic groups, particularly impacting children growing up in impoverished environments. Home visitation intervention programs, such as the Home Instruction for Parents of Preschool Youngsters (HIPPY), have been used for decades to improve academic readiness in these vulnerable preschool‐aged children. Although the benefits of HIPPY on academic readiness and performance are well‐documented, there has been no examination of social‐emotional benefits to participating parent‐child dyads. This study followed a HIPPY cohort over the course of 1 year to evaluate change in maternal and child social‐emotional and behavioral functioning. Program participants demonstrated reduced parental stress and depression and increased parental social connection as well as reduced child externalizing behaviors and improved child adaptive functioning over the course of the program, even in the context of the COVID‐19 pandemic and associated lockdown. These data highlight the additional benefits of early home‐based academic intervention programs. Resumen: Las significativas disparidades en educación y resultados socioemocionales existen entre grupos raciales/étnicos, ejerciendo particularmente un impacto en los niños que crecen en ambientes empobrecidos. Los programas de intervención de visitas a casa, tales como la Instrucción en el Hogar para Padres y Niños Pequeños en Edad Prescolar (HIPPY), han sido utilizados por décadas para mejorar la preparación académica en estos niños de edad prescolar vulnerables. A pesar de que los beneficios de HIPPY en cuanto a preparación y rendimiento académicos están bien documentados, no se ha dado una revisión de los beneficios socioemocionales para las díadas progenitor‐niño que participan. Este estudio le dio seguimiento a un grupo de HIPPY a lo largo del curso de un año para evaluar el cambio en el funcionamiento socioemocional y de comportamiento materno y en el niño. Los participantes en el programa demostraron un reducido nivel de estrés y depresión en progenitores y un aumento en la conexión social de progenitores, así como niveles reducidos de comportamiento externalizantes en el niño y un incremento en el funcionamiento de adaptación del niño a lo largo del curso del programa, aun dentro del contexto de la pandemia del COVID‐19 y el aislamiento que con ella se asocia. Estos datos subrayan los beneficios adicionales de programas tempranos de intervención académica en casa. Résumé: Des inégalités importantes dans l'éducation et les résultats socio‐émotionnels existent entre les groupes raciaux/ethniques, ce qui impacte particulièrement les enfants grandissant dans des milieux appauvris. Des programmes d'intervention de visite à domicile, comme le programme d'Instruction à Domicile de Parents de Jeunes Enfants d'Age Préscolaire (abrégé HIPPY en anglais), ont été utilisés depuis des dizaines d'années afin d'améliorer la préparation académique de ces enfants vulnérables d'âge préscolaire. Bien que les bénéfices du programme HIPPY sur la préparation académique et la performance académique soit bien documentée, les bénéfices socio‐émotionnels de la participation des dyades parent‐enfant n'ont jamais été examinés. Cette étude a donc suivi une cohorte HIPPY au cours d'une année afin d'évaluer le changement dans le fonctionnement émotionnel et comportemental maternel et de l'enfant. Les participantes ou participants au programme ont fait preuve d'une réduction du stress parental et de la dépression et de plus de lien social parental ainsi qu'une réduction de comportements d'externalisation de l'enfant et d'un fonctionnement adaptatif de l'enfant amélioré au cours du programme, même dans le contexte de la pandémie du covid‐19 et du confinement. Ces données mettent en évidence les bénéfices supplémentaires des programmes d'intervention académique précoce à domicile. Zusammenfassung: Wirksamkeit eines Peer‐basierten häuslichen Erziehungsprogramms für die Verbesserung sozial‐emotionaler Outcomes bei Eltern und Kindern Zwischen verschiedenen ethnischen Bevölkerungsgruppen bestehen erhebliche Ungleichheiten in Bezug auf Bildung und sozial‐emotionale Outcomes, was sich insbesondere auf Kinder auswirkt, die in einem verarmten Umfeld aufwachsen. Hausbesuchsprogramme wie das Programm „Home Instruction for Parents of Preschool Youngsters" (HIPPY) werden seit Jahrzehnten eingesetzt, um die schulischen Leistungen dieser gefährdeten Kinder im Vorschulalter zu verbessern. Der Nutzen von HIPPY für die akademische Leistungsbereitschaft und die Leistung an sich ist gut dokumentiert. Der sozial‐emotionale Nutzen für teilnehmende Eltern‐Kind‐Dyaden wurde bisher allerdings noch nicht untersucht. Diese Studie verfolgte eine HIPPY‐Kohorte über ein Jahr hinweg, um Veränderungen im sozial‐emotionalen Bereich und im Verhalten von Müttern und Kindern zu untersuchen. Die Programmteilnehmenden zeigten eine Verringerung des elterlichen Stresses und depressiver Symptomatik. Außerdem wurde eine stärkere soziale Bindung der Eltern sowie eine Verringerung externalisierenden Verhaltens der Kinder und eine Verbesserung der Anpassungsfähigkeit der Kinder im Verlauf des Programms festgestellt, selbst im Kontext der COVID‐19‐Pandemie und des damit verbundenen Lockdowns. Diese Daten unterstreichen den zusätzlichen Nutzen von auf Hausbesuchen basierenden, frühen akademischen Interventionsprogrammen. 抄録: 親と子の社会情動発達を改善するピア(仲間)ベースの在宅教育プログラムの有効性 教育および社会情動発達には人種/民族群間の著しい格差が存在し、特に貧困環境で育つ子どもたちへ影響を及ぼしている。HIPPY(Home Instruction for Parents of Preschool Youngsters) のような家庭訪問介入プログラムは、これらの脆弱な就学前年齢の児童の就学準備の改善のために、数十年前から活用されてきた。HIPPYが就学準備と成績に有益であることは十分に立証されているが、参加している親‐子の社会情動への恩恵についてはこれまで検討されてこなかった。本研究では、HIPPYのコホートを1年間追跡し、母そして子どもの社会情動面及び行動面の機能の変化を評価した。COVID‐19パンデミックとそれに伴うロックダウン下でも、プログラム参加者は、プログラムの期間を通して、親のストレスと抑うつの減少、親の社会とのつながりの増加、さらに子どもの問題行動の減少、子どもの適応的機能の向上を実証した。これらのデータは、早期の在宅学業介入プログラムのさらなる効用を強調するものである。 摘要: 在教育和社交情绪发展方面, 种族或族裔群体之间存在显著差异, 这对在贫困环境中成长的儿童影响尤其大。几十年来, 家访干预计划, 如"学龄前儿童父母家庭指导" (HIPPY), 一直被用于改善这些弱势学龄前儿童的学业准备。尽管HIPPY在学业准备和表现方面的益处有充分的文献证明, 但尚未对参与计划的亲子二元组在社交情感方面的益处进行研究。本研究对HIPPY群体进行了为期一年的跟踪调查, 以评估父母及儿童社交情感和行为功能的变化。即使在COVID‐19大流行和相关封锁的背景下, 计划参与者在过程中也表现出父母压力和抑郁的减轻, 父母社会联系的增加, 以及儿童外化行为的减少和儿童适应功能的改善。这些数据突显了早期家庭学术干预计划的额外益处。 ملخص: فاعلية برنامج التعليم المنزلي القائم على الأقران في تحسين النتائج الاجتماعية العاطفية للوالدين والأطفال توجد تفاوتات كبيرة في التعليم والنتائج الاجتماعية والعاطفية بين المجموعات العرقية/ الإثنية ، ولا سيما التي تؤثر على الأطفال الذين ينشأون في بيئات فقيرة. وقد تم استخدام العديد من برامج التدخل للزيارات المنزلية ، مثل برنامج التعليم المنزلي لأولياء أمور أطفال ما قبل المدرسة (HIPPY) ، لعقود من الزمن لتحسين الاستعداد الأكاديمي لدى هؤلاء الأطفال المعرضين للمخاطرة في سن ما قبل المدرسة. على الرغم من أن فوائد برنامج HIPPY من حيث الإعداد الأكاديمي والأداء موثقة جيدًا ، إلا أنه لم يتم فحص الفوائد الاجتماعية والعاطفية لثنائيات الوالدين والطفل المشاركين. اتبعت هذه الدراسة مجموعة HIPPY على مدار عام واحد لتقييم التغيير في الأداء الاجتماعي والعاطفي والسلوكي للأم والطفل. أظهر المشاركون في البرنامج انخفاضًا في إجهاد الوالدين والاكتئاب وزيادة في التواصل الاجتماعي الوالدي بالإضافة إلى انخفاض سلوكيات الطفل العدائية وتحسين الأداء التكيفي للطفل على مدار البرنامج ، حتى في سياق جائحة كوفيد ‐19 والإغلاق المرتبط به. تسلط هذه النتائج الضوء على الفوائد الإضافية لبرامج التدخل الأكاديمي المنزلي المبكر.